Immediate rehabilitation with feeding appliance of a three day old neonate with cleft lip and palate- a case report - Kapoor, Deepika; Garg, Deepanshu (Journal of College of Medical Sciences-Nepal, 2017)
Orofacial clefts (OFC) are one of the most common congenital problems seen with a very high incidence. It imparts a negative effect on the overall health of the child by hindering in his feeding practices, normal facial growth, development of dentition and hence speech. Infants born with orofacial clefts have oronasal communication which creates a problem with the creation of negative pressure inside the oral cavity required for suckling. The treatment for such patients is with the multidisciplinary approach but the preliminary concern for the neonate is to help with the feeding for which a feeding appliance is given. This case report presents a case of a 3-day old infant to whom a feeding appliance was given to aid in suckling.